Teachers’ and students’ attitude to the use of information communication technology in english language instruction in senior secondary schools in Abeokuta metropolis (2013)
"The integration of ICT into education is desirable but it has not been fully exploited in the teaching and learning of English language in many secondary' schools in Nigeria. This may not be unconnected with their attitude towards this modern innovation. Against this background, this study aimed at investigating the attitude of teachers and students to the use of Information and Communication Technology (ICT) in teaching and learning English at die Senior Secondary School level in Abeokuta. This study adopted a descriptive research design method while simple random sampling technique was used to select 22 out of 74 senior secondary schools in die area. A total of 45 teachers and 296 students were sampled and data were obtained through two distinct instruments designed for the purpose. The reliability co-efficient of the instruments were .75 and .69 respectively. Descriptive statistics of frequency counts and percentages were used to analyze the data. the results revealed that teachers have positive attitude to die use of ICT in teaching while students believed it should be for only those in the sciences. Also, it revealed that the commonest ICT facilities being used by the respondents were computer and mobile phones while teachers believed that ICT could be used to teach all aspects of English. On the basis of this, it was recommended that the use of ICT should be encouraged in teaching English in schools. "